Effect of incomplete blinking on tear film stability. - Hirota, Masakazu; Uozato, Hiroshi; Kawamorita, Takushi; Shibata, Yuko; Yamamoto, Shinya (Optometry & Vision Science, 2013)
Purpose: The purpose of this study is to assess changes in tear film stability caused by incomplete blinking.Methods: Eleven subjects (mean age, 21.3 years) participated in this study. All subjects had a visual acuity of 20/20 or better and normal ocular health. The subjects were asked to play a game for 60 min on a personal computer as part of a visual display terminal (VDT) experiment. Each subject's blinking was observed by a Web camera that was attached to the top of the display. Every 15 min, the VDT experiment was interrupted for measurement. An RT-7000 (Tomey Co., Ltd., Nagoya, Japan) was used to measure ring breakup time as a parameter of tear film stability. An OPD-Scan II ARK-10000 (NIDEK Co., Ltd., Aichi, Japan) was used to measure corneal aberrations.Results: Although the total blink rate changed very little, the complete and incomplete blink rates fluctuated during the VDT experiment. Both types were plotted along symmetrical cubic approximation curves. Noninvasive (ring) breakup time at 30 min (4.33 ± 2.57 s) was significantly shorter (p < 0.01) than that at baseline before the VDT experiment (8.62 ± 1.54 s). After 30 min, the incomplete blink rate began decreasing (fewer incomplete blinks), whereas the complete blink rate began increasing. Ring breakup time increased (improved) after 45 min; however, the incomplete blink rate began to increase again after approximately 50 min.Conclusions: Even if the total blink rate decreases, the tear film remains stable so long as almost all blinks are complete. The incomplete blinking contributes to tear film instability and is variable with prolonged VDT exposure. Our study indicated that the tear film stability was determined by blinking quality, and the predominance of blinking type relates to tear film stability.